Reverse logistics in the textile industry: a systematic review of the main barriers to its implementation - Pérez Palacios, María Stephany; Mamani Jauregui, Sara Paola; Elugo Guevara, Christian; Valdiviezo Gonzales, Lorgio (LACCEI, 2025)
The textile industry, driven by the fast fashion model, has had a significant environmental impact due to high waste generation and low recycling rates. In this scenario, reverse logistics emerges as a key strategy for promoting sustainability, enabling the return and reuse of textile products. However, its implementation faces multiple barriers, especially in countries with emerging economies. This review seeks to identify and categorize the main challenges and strategies associated with the adoption of reverse logistics in the textile sector, considering the differences between economic contexts. To this end, the PICO methodology was applied to formulate the exploratory questions, and the PRISMA protocol was used to ensure a rigorous selection process. A total of 777 articles from Scopus, ScienceDirect, and Web of Science were analyzed. Of that total, 31 studies were selected for meeting the established criteria. The findings reveal that the main barriers are technological, economic, and infrastructural, being more pronounced in developing countries. In addition, limited technological adoption, poor technical training, and low consumer participation were identified. The study concludes that the effective implementation of reverse logistics requires a comprehensive approach that combines technological innovation, clear public policies, and business commitment.